Afforestation by natural regeneration or by tree planting: examples of opposite hydrological impacts evidenced by long-term field monitoring in the humid tropics - Lacombe, Guillaume; Ribolzi, Olivier; Rouw, Anneke de; Pierret, Alain; Latsachak, K.; Silvera, N.; Pham Dinh, R.; Orange, Didier; Janeau, Jean L.; Soulileuth, B.; Robain, H.; Taccoen, A.; et al. (Copernicus GmbH, 2015)
The humid tropics are exposed to an unprecedented modernization of agriculture involving rapid and highly-mixed land-use changes with contrasted environmental impacts. Afforestation is often mentioned as an unambiguous solution for restoring ecosystem services and enhancing biodiversity. One consequence of afforestation is the alteration of streamflow variability controlling habitats, water resources and flood risks. We demonstrate that afforestation by tree planting or by natural forest regeneration can induce opposite hydrological changes. An observatory including long-term field measurements of fine-scale land-use mosaics and of hydro-meteorological variables has been operating in several headwater catchments in tropical Southeast Asia since 2001. The GR2M water balance model repeatedly calibrated over successive 1 year periods, and used in simulation mode with specific rainfall input, allowed the hydrological effect of land-use change to be isolated from that of rainfall variability in two of these catchments in Laos and Vietnam. Visual inspection of hydrographs, correlation analyses and trend detection tests allowed causality between land-use changes and changes in seasonal flows to be ascertained. In Laos, the combination of shifting cultivation system (alternation of rice and fallow) and the gradual increase of teak tree plantations replacing fallow, led to intricate flow patterns: pluri-annual flow cycles induced by the shifting system, on top of a gradual flow increase over years caused by the spread of the plantation. In Vietnam, the abandonment of continuously cropped areas mixed with patches of tree plantations led to the natural re-growth of forest communities followed by a gradual drop in streamflow. Soil infiltrability controlled by surface crusting is the predominant process explaining why two modes of afforestation (natural regeneration or planting) led to opposite changes in flow regime. Given that commercial tree plantations will continue to expand in the humid tropics, careful consideration is needed before attributing to them positive effects on water and soil conservation.